2021
DOI: 10.1002/agg2.20206
|View full text |Cite
|
Sign up to set email alerts
|

Corn response to tillage and side‐dress nitrogen management on claypan soil

Abstract: Since information islimited regarding N management and tillage options for corn (Zea mays L.) grown on claypan soil in the eastern Great Plains, the objective of this study was to determine the effect of preplant and side-dress N applications on corn grown in conventional-and no-till systems. The yield penalty for no-till grown corn was nearly 20% due partially to an 8% stand reduction, but also to lower kernel weight and kernels ear -1 than with conventional till. These yield and yield component reductions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The significant reductions in yearly corn yield with no-till compared with conventional tillage were as great as 56%, and the yield penalty for no-till averaged more than 25% across all years. Even though corn was rotated with wheat and doublecrop soybean in this study, this yield penalty is similar to the 3-yr yield reduction of nearly 20% with no-till compared with conventional tillage for continuous corn on a claypan soil (Sweeney & Ruiz Diaz, 2021). On a clay loam soil, Messiga et al (2012) reported that corn grain yields with notill were reduced by 10-25% in an 11-yr study.…”
Section: Corn Yieldsupporting
confidence: 64%
See 1 more Smart Citation
“…The significant reductions in yearly corn yield with no-till compared with conventional tillage were as great as 56%, and the yield penalty for no-till averaged more than 25% across all years. Even though corn was rotated with wheat and doublecrop soybean in this study, this yield penalty is similar to the 3-yr yield reduction of nearly 20% with no-till compared with conventional tillage for continuous corn on a claypan soil (Sweeney & Ruiz Diaz, 2021). On a clay loam soil, Messiga et al (2012) reported that corn grain yields with notill were reduced by 10-25% in an 11-yr study.…”
Section: Corn Yieldsupporting
confidence: 64%
“…In contrast, sometimes lower no‐till yield is not related to lower population (Iragavarapu & Randall, 1995) or lower population with no‐till does not reduce yields (Kapusta et al., 1996). For continuous corn, Sweeney and Ruiz Diaz (2021) found that while lower population could account for some of the yield decline with no‐till, lower number of kernels per ear and kernel weights also contributed to the reduced grain yield. However, in this study, tillage system had little or no significant effect on the remaining yield components (Table 4).…”
Section: Resultsmentioning
confidence: 99%